Factors constraining effective application of ICTs in teachers ' training colleges in Tanzania - Nchahoruri, Joel F; Mungwabi, Hosea (University of Dar es Salaam Library Journal, 2016)
This study investigated the impediments to the effective application of ICTs in Tanzania ' s teachers ' training colleges (TTCs). It was conducted in 2015 at Bunda, Butimba, Morogoro, Murutunguru TTCs and the Ministry of Education and Vocational Training headquarters. Data were collected from 134 students, tutors and other officials using questionnaires, interviews, focus group discussions, and observations. The study established purposes for which respondents made use of the pedagogical ICTs and identified the constraints that hamper the adoption of ICTs to be unreliable connectivity, inadequate pedagogical skills, low broadband, lack or inadequate technical support, lack of necessary ICT equipments or unreliable ICT equipments/facilities and power interruption. Basing on these findings, the study recommends recruiting ICT technicians for technical support, providing adequate and reliable ICT facilities, improving power supply to colleges, and ensuring reliable connectivity to colleges in a bid to to enhance pedagogical ICT integration in teachers ' training colleges.